GAMBARAN TINGKAT KECEMASAN PADA LANSIA PENDERITA HIPERTENSI DI JALAN PEMBANGUNAN USU LINGUKUNGAN 14 KECEMATAN MEDAN BARU TAHUN 2021 - Hotmarina Lumban Gaol; Irna Berna Irawaty br Marmata (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
As you get older, there will be many diseases suffered due to a decrease in various functions of the body. One of the diseases that commonly suffered by the elderly people are hypertension. Hypertension can disturb phychological condition because of fear and anxiety. This research aims to know the level of anxiety in the elderly people with hypertension street Pembangunan USU Environment 14 Districts Medan Baru in 202. The design of this research use descriptive observational study with 25 questions as an instrument. The samples on this research was total sampling with all respondents 35 people. In street Pembangunan USU Environment 14 Districts Medan Baru. The results of the study obtained that most respondents experienced moderate levels of anxiety, namely 21 respondents and a small proportion of respondents experienced panic, namely 5 respondents. All respondents suffered from anxiety wit range mild anxiety to panic. Most respondets experienced moderate anxiety with first degree hypertension. It is advisable for the next researcher to examine correlation between the degree of hypertension and the level of anxiety. Health workers should be able to identify anxiety in elderly people with Hipertension and be able to provide solutions to overcome anxiety.